Rheumatological presentation of Bartonella koehlerae and Bartonella henselae bacteremias: A case report. Issue 17 (April 2018) - Mozayeni, Bobak Robert; Maggi, Ricardo Guillermo; Bradley, Julie Meredith; Breitschwerdt, Edward Bealmear
Abstract: Introduction: Systemic Bartonella spp. infections are being increasingly reported in association with complex medical presentations. Individuals with frequent arthropod exposures or animal contact appear to be at risk for acquiring long standing infections with Bartonella spp. Case report: This case report describes infections with Bartonella koehlerae and Bartonella henselae in a female veterinarian whose symptoms were predominantly rheumatologic in nature. Infection was confirmed by serology, polymerase chain reaction (PCR), enrichment blood culture, and DNA sequencing of amplified B koehlerae and B henselae DNA. Long-term medical management with antibiotics was required to achieve elimination of these infections and was accompanied by resolution of the patient's symptoms. Interestingly, the patient experienced substantial improvement in the acquired joint hypermobility mimicking Ehlers–Danlos Syndrome (EDS) type III. Conclusion: To facilitate early and directed medical interventions, systemic bartonellosis should potentially be considered as a differential diagnosis in patients with incalcitrant rheumatological symptoms and frequent arthropod exposures or extensive animal contact.